Uma possível “simbiose”: vadios e capoeiras em Alagoas (1878-1911) - Barbosa, Gustavo Bezerra (2017)
This paper is in History Knowledge area. This study seeks to write a Social History of Culture, so has the understanding that this dimension of historical knowledge comprises the study of the practices, representations, the symbolic, short, seeks understand the culture of social relations. The research aims to investigate vagrants and barns in Alagoas, more particularly in Maceio during the period 1878 to 1911. Therefore, this study focuses primarily on the criminal code (1830) and criminal (1890), the municipal ordinances of Maceió 1878 and 1911, the provincial president of reports and information in the newspapers published in the capital Alagoas in the final years of the empire until the early years of the republic. The survey was conducted from documentation from various sources and a qualitative analysis approach, because we believe that this allows us perceive the different social interactions present in contexts where vagrants and barns fall historically. It takes as hypothesis in this research the existence of a "symbiosis" between vagrants and barns, where it gets you noticed in the analysed documentation. The path to the development and analysis of this question has reference the evidentiary paradigm of Carlo Ginzburg. Through this method performed a study of documentary material, making it possible to approach the relevant reality stray experience and barns. On other hand, the method also helps us to question the invisible structures within which stray and barns were entered.